Posługa słowa w epoce mediów - Siwek, Gerard (Studia Pastoralne, 2026)
The author of the article deals with the issue of a relation of the Church’s ministry of the Word and abruptly developing mass media. His starting point is a positive impact of media on preaching, especially with respect to immense widening of the scope of its influence. The author encourages readers to use mass media in a broadly understood evangelisation. On the other hand he draws readers’ attention to a potential negative impact of mass media on preaching. Influence of mass media may reduce an awareness of divine dimension of preaching, contribute to vanishing of theological understanding of functions of preachers of the Word, adjusting the preached truth to media standards, domination of a picture over a word. Also, the author recognises a need of enhancing traditional aims of preaching by new ones, such as developing reflection skills, showing a difference between a real and virtual world, warning against ethical relativism, defying consumerism, increasing awareness of other people’s needs.